AWARENESS AND RESPONSE OF GAYO HIGHLANDS COFFEE FARMERS TOWARDS THE DYNAMICS OF CLIMATE CHANGE - Baihaqi, Akhmad; Agussabti, Agussabti; Atikah, Qhisthina; Ginting, Aisyah Amira (Universitas Veteran Bangun Nusantara, 2024)
Arabica coffee farmers in Central Aceh and Bener Meriah districts rely on income sources from Arabica coffee plantations which are very vulnerable to climate change. The perception of Arabica coffee farmers to understand the negative impacts caused by climate change and how the adaptation efforts carried out will determine the success of Arabica coffee farmers to survive developing their coffee plantations. The purpose of this study is to find out how the perception and adaptation of Arabica coffee farmers to climate change and how the relationship between the perception and adaptation variables. Purposive sampling, namely Arabica coffee farmers under the guidance of CV. Oro Kopi Gayo and KSU Sara Ate, as many as 67 farmers. The research data were analyzed descriptively quantitative with a Likert scale analysis tool and tested using the Spearman correlation. The results of the study showed that positive Arabica coffee farmers perception on climate change which means farmers know the issue of climate change and feel its effect on Arabica coffee plants, especially the quality and productivity of Arabica coffee with knowledge indicator values of (78.12%), experience indicators (92.42%), and indicators of expectation (80.10%). However, adaptation made by farmers to climate change is still relatively low with a physical adaptation indicator value of (37.81%), environmental adaptation indicator of (47.19%), and institutional adaptation indicators of (32.18%). The relationship between perception and adaptation showed significance results of 0.838, which means the relationship between the perception and adaptation variables were not significant or meaningless. Keywords: Climate Change, Perception, Adaptation, Farmers Arabica Coffee, Gayo Highlands